2012
DOI: 10.2527/jas.2012-5266
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oxidized corn oil and a synthetic antioxidant blend on performance, oxidative status of tissues, and fresh meat quality in finishing barrows

Abstract: The objective was to evaluate the effect of feeding oxidized corn oil with or without a dietary antioxidant (AOX) on performance, tissue oxidative status, and meat quality in barrows. One hundred sixty barrows were arranged in a 2 × 2 factorial of treatments in a complete randomized block design with 8 pens per treatment and 5 pigs per pen. Diets contained 5.0 mg/kg of 1 of 2 types of corn oil (fresh or oxidized) with or without antioxidant. Final oxidized oil was produced in a heated container by continuously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
72
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(107 citation statements)
references
References 32 publications
27
72
7
1
Order By: Relevance
“…The same result on G:F was observed. In disagreement with the present data, Boler et al (2012) reported that dietary supplementation with oxidized corn oil for 56 d in barrows reduced ADG and BW. This should be related to the different length of dietary supplementation and substance inducing oxidative stress.…”
Section: Discussioncontrasting
confidence: 99%
“…The same result on G:F was observed. In disagreement with the present data, Boler et al (2012) reported that dietary supplementation with oxidized corn oil for 56 d in barrows reduced ADG and BW. This should be related to the different length of dietary supplementation and substance inducing oxidative stress.…”
Section: Discussioncontrasting
confidence: 99%
“…Restoration to nearly normal concentrations of MDA by antioxidant blend may be due to an enhancement of the body's antioxidant defense system. This result is consistent with a previous swine study in which an elevation of TBARS was found after oxidized oil was applied, whereas AOX reduced plasma and muscle TBARS (Boler et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…Birds were fed a common commercial-type diet until day 8. Oxidized oil induced oxidative stress in animals [22], which can then cause tendon damage [20]. To exacerbate the stress to tendon, birds in one pen ( Figure 1B) were fed oxidized fat diet that included 5% oxidized soybean oil starting on day 8.…”
Section: Bird Trials and Tissue Sample Preparationmentioning
confidence: 99%
“…Oxidative stress has been reported to exacerbate joint disease in a rat arthritis model [20] and associate with cartilage degeneration in an experimental canine model of osteoarthritis [21]. Dietary oxidized oil has been reported to induce oxidative stress in animals [22].…”
Section: Introductionmentioning
confidence: 99%